Marketing plan for UP ITTC's e-learning project - Endriga, Victor A. (Technology Management Center, 2012)
The UP Information Technology Training Center (UP ITTC) has begun to venture into e-learning in an effort to increase the Center's accessibility, impact and reach. E-learning is generally defined as any form of teaching and learning that is supported electronically. However, e-learning in this case would consist entirely of web based technology to aid in distance learning. The Center will use content management systems and free and open-source learning for its online delivery of current courses and future offerings. Using these systems will also supplement face-to-face instruction and enhance the effectiveness of UP ITTC's proven teaching techniques and methods. Combining the old and the new strategies, should promote interaction among instructors, students and facilitators that could pave way for a collaborative project-based approach to learning. Aside from its aim to provide training to a larger audience/market, the reusability and availability of the online content give learners sufficient time to digest complex technical concepts. This would also address some of the UP ITTC students' issue in understanding concepts that seem difficult given the fast pace of classroom instruction. Most importantly, offering certificate courses and specialist tracks online will also cater to IT professionals or those wanting to shift to an IT career but cannot enroll full-time because of time, distance, financial constraints, or other limitations like present employment. The UP ITTC's e-learning initiative shall expand its target market, opening growth opportunities for the Center as online offerings can provide additional and potentially substantial source of avenue. Currently, the e-learning site is being used to supplement face-to-face instruction. Since the system is already up and running, this paper aims to determine the pricing, marketing and operational processes needed so that the e-Learning system will be utilized to its full potential. This means that it will not only supplement face-to-face instruction but it will also enable the system to provide a complete distance learning experience to students.